The mutability of fiction descriptors: the evolution of 'pulp'. (1st September 2022) - Hider, Philip; Bourke, Leonie
Abstract : The term 'pulp' is rarely used in library cataloguing as a descriptor for fiction and does not appear in indexing vocabularies such as the Library of Congress Genre/Form Terms (LCGFT). In contrast, it is used extensively as a tag for large numbers of fiction titles in social cataloguing sites such as LibraryThing and Goodreads. We explore the reasons for the library world's reluctance to adopt the term, with reference to the history of the term and the fiction it represents. We then report on a comparative thematic analysis of LibraryThing user reviews of 'old' and 'new' pulp, uncovering an evolution in the way the term has been used. Its more positive usage in contemporary descriptions suggests that pulp's exclusion from LCGFT should be reviewed.